Knowledge and pacification on the U.S. conquest and the writing of Philippine history - Ariate, Joel F., Jr (Kasarinlan: Philippine Journal of Third World Studies, 2018)
Access online through this link: https://journals.upd.edu.ph/index.php/kasarinlan/article/view/7071/6156